2022
DOI: 10.36941/ajis-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Governance Mechanism, Company Characteristics on the Timeliness of Financial Statements: Evidence from Listed Companies in Vietnam

Abstract: This study aims to determine the factors affecting the timeliness of financial statements from the perspective of company characteristics and corporate governance mechanism. We examined the panel data from financial statements and annual reports of 172 Vietnamese companies listed on HOSE and HNX from 2014 to 2020 and found that company size had a negative impact on the timeliness of financial statements, while profitability had a positive impact. Besides, the findings also showed that board ownership and audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…On the other hand, Ebaid (2022) found that the timing of financial reports is significantly related to three of the company's characteristics, namely size, profitability and leverage, while there was no significant effect of ownership. Efobi and Okougbo (2014) and Hoang, Pham, Thalassinos, and Le (2022) found a negative relationship between the firm size, leverage, performance, and timeliness of financial reporting, while firm age was positive. While Aigienohuwa andEzejiofor (2021), andNovandalina, Ernawati, andBudiyono (2022) found that leverage had no effect on the timeliness of financial reporting.…”
Section: Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, Ebaid (2022) found that the timing of financial reports is significantly related to three of the company's characteristics, namely size, profitability and leverage, while there was no significant effect of ownership. Efobi and Okougbo (2014) and Hoang, Pham, Thalassinos, and Le (2022) found a negative relationship between the firm size, leverage, performance, and timeliness of financial reporting, while firm age was positive. While Aigienohuwa andEzejiofor (2021), andNovandalina, Ernawati, andBudiyono (2022) found that leverage had no effect on the timeliness of financial reporting.…”
Section: Literature Reviewmentioning
confidence: 95%
“…The timeliness of accounting information seems to be an essential attribute in and of itself, however, it is becoming a more important issue now than ever before as a result of the phenomenal changes in both modern technology and business practices. In the current economic scenario, the importance of timely accounting information for economic reasons in general and capital markets in particular cannot be ignored (Oraka et al, 2019;Hoang et al, 2022). Despite this, there are some worrying trends regarding the time taken to release financial reports.…”
Section: Timing Of Reporting and The Role Of Digitalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Disaster operations are critical and complex, and this necessitates strong decisionmaking that is aided by information technology, particularly Artificial Intelligence (ADB and OECD, 2020;Altay and Green, 2006;Pham et al, 2022). Advances in Machine Learning (ML) and Deep Learning (DL) have been utilised in recent years to address the scale and impact of disasters through effective and informed disaster management (Sun et al, 2020;Thalassinos et al, 2022). Over time, disaster management addresses them (Van Wassenhove, 2006).…”
Section: Disaster Management Using Machine Learning and Deep Learningmentioning
confidence: 99%